Polyaromatic hydrocarbons in aquafeeds, source, effects and potential implications for vitamin status of farmed fish species: a review. (26th March 2015) - Berntssen, M.H.G.; Ørnsrud, R.; Hamre, K.; Lie, K.K.
Abstract: Access to marine feed ingredients is considered a limiting factor for the rapidly growing aquaculture industry. With increasing inclusion of vegetable feed ingredients in aquafeeds, new challenges have arisen. Substituting marine oils and meals with vegetable ingredients has decreased the level of persistent organic pollutants (POPs) in marine farmed fish such as Atlantic salmon. Consequently, this shift in feed ingredients has led to increased levels of polyaromatic hydrocarbons (PAHs) in aquafeeds. Several of the PAHs listed are on EFSAs and EPAs list of priority substances. Not only are the carcinogenic and genotoxic properties of PAHs of concern, but also their ability to interact with and disrupt metabolic pathways such as vitamin metabolism and signalling. The interactions, and the potential depletion of vitamin stores that follows, are of particular interest as marine ingredients are naturally rich in micronutrients such as vitamins A and D. This study has summarized the current knowledge on the effect of PAHs commonly found in vegetable feed ingredients on vitamin metabolism/signalling and their possible implications in fish.